Efforts to Improve Science Learning Outcomes Through Model Problem Based Learning (PBL) Class VI SD Negeri Losari Kidul 02 - Safii, Ujang (Universitas Sebelas Maret, 2020)
This Classroom Action Research is an effort to improve student learning outcomes on the magnetic properties of science subject content through themodel Problem Based Learning. This research was conducted on the sixth grade students of SD Negeri Losari Kidul 02. This research was motivated by the teacher not using learning models and media. The learning model used is too conventional and in teaching does not use media during the learning process. Student learning outcomes are still low, many students score below the KKM in science learning as measured by a test at the end of the lesson. This study uses Classroom Action Research (CAR) with steps consisting of planning, implementation, observation, and reflection in each cycle. This research was conducted in two cycles. In each cycle, learning activities are carried out by applying thelearning model Problem Based Learning. This research shows that students' learning outcomes in the matter of magnetic properties through themodel Problem Based Learning can increase. This increase can be seen from the results of classroom action research in cycles I and II. In the first cycle of students who completed KKM 70 as many as 58.7% (10 people from 17 students). In cycle II, students who completed KKM 70 were 88.1% or 15 of 17 students. The conclusion obtained in this study is that the use oflearning models Problem Based Learning can improve learning outcomes in science learning material magnetic properties in class VI students of SD Negeri Losari Kidul 02.